Success Factors for Humanitarian Access: Quantitative Case Studies of ICRC Visits to Detainees - Kouta Futsuki; Takashi Sekiyama (Frontiers in Political Science, 2022)
The importance of humanitarian access has been widely recognized by practitioners and scholars. Nevertheless, the factors behind its success have been not yet fully clear. This study, therefore, conducted a quantitative analysis of the International Committee of the Red Cross's (ICRC) access to detainees' visits to elucidate the success factors of humanitarian access. It analyzed a government's attributes that grant the ICRC access and engagements to soften the government's refusal of its access. The results revealed the following findings: (1) a government's capacity is required to an extent to keep public services in armed conflict; (2) material incentive (MI) in a government is working, and the ICRC assistance for civilians is effective; (3) conceptual incentive (CI) to seek the international legitimacy is irrelevant; (4) conceptual disincentive (CD) to avoid disclosure of the government's violation of humanitarian norms is working, and a high-level meeting with the ICRC is less likely to lessen the government's concern. These findings supplement insights of previous research on general humanitarian access in a quantitative way, implying the possibilities and the limits of humanitarian agency's engagements. Further research on various types of humanitarian success can clarify its success factors in a more specific way.